2001
DOI: 10.1542/peds.107.6.e90
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Change to Inactivated Poliovirus Vaccine on the Immunization Status of Young Children in the United States: A Study From Pediatric Research in Office Settings and the National Medical Association

Abstract: Study children who were >12 months of age at the time that data were collected were categorized as being fully immunized at 12 months if they had received the same vaccines before their first birthday. To assess the effect of type of poliovirus vaccines on these outcomes, study patients were classified as being in an IPV or OPV group based on the initial type of vaccine received. Logistic regression was used to calculate the odds ratios (ORs) and 95% confidence intervals (CIs) for IPV as a predictor of being f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 13 publications
(6 reference statements)
0
10
0
Order By: Relevance
“…Minority representation averaging 15% in the early 1990s 15,16 has risen to proportions in excess of 30% during the past 5 years. 17,18 With respect to Hispanic ethnicity, although the percentage of Hispanic patients in the PROS sample was not significantly different from the NAMCS sample, the difference bordered on significance, suggesting a continuing need to ensure Hispanic representation in PROS studies.…”
Section: Discussionmentioning
confidence: 89%
“…Minority representation averaging 15% in the early 1990s 15,16 has risen to proportions in excess of 30% during the past 5 years. 17,18 With respect to Hispanic ethnicity, although the percentage of Hispanic patients in the PROS sample was not significantly different from the NAMCS sample, the difference bordered on significance, suggesting a continuing need to ensure Hispanic representation in PROS studies.…”
Section: Discussionmentioning
confidence: 89%
“…The transition was gradually accepted with no decreases in vaccination coverage or increases in adverse events. [37][38][39][40] Following this change, all forms of poliomyelitis have been eliminated in the United States; the last imported case occurred in 1993 and the last VAPP case in 1999. The only threats from polio in the United States are from laboratories and the few remaining polio-endemic areas in Africa and Asia.…”
Section: Impact Of Poliovirus Vaccine Policy Changesmentioning
confidence: 99%
“…[3][4][5][6] Studies of previously introduced vaccines have examined parental and pediatrician compliance by determining whether children are up-to-date with their immunizations. [7][8][9][10] However, to our knowledge, no previous studies have attempted to determine whether pediatricians' self-reported practices are themselves adherent to national immunization recommendations.…”
mentioning
confidence: 99%